A method for preparing powder sintered foil
By spraying the modified alumina suspension on the surface of the aluminum foil, the adhesion problem of powder sintered foil in the heat treatment stage is solved, and the normal expansion of the foil layer and high-performance sintering effect are achieved.
Patent Information
- Application Number
- CN202411960099.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The adhesive in the powder sintered foil melts and volatilizes during the heat treatment stage, resulting in adhesion between the aluminum foil layers. After sintering, the foil roll cannot unfold normally, resulting in product scrapping.
The modified alumina suspension is sprayed on the surface of the coated and dried aluminum foil to isolate the aluminum foil that is tightly attached due to winding and prevent adhesion.
After sintering, there is no adhesion between the foil layers, no tearing or breaking of the foil layer occurs during rolling, and the voltage resistance, capacity and leakage current are maintained at normal levels.
Smart Images

Figure CN119368744B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sintered aluminum foil, and in particular to a method for preparing a powder sintered foil. Background Art
[0002] In recent years, powder sintered anode foil has become a hot topic of research due to its ultra-high specific volume and low environmental pollution. The technical route of powder sintered foil is opposite to that of traditional corrosion foil. It uses additive manufacturing to attach aluminum powder particles to the surface of the base aluminum foil and sinter and solidify it. The gaps between the particles form a larger specific surface area than traditional corrosion foil, which greatly improves the electrical properties of the anode foil. Compared with the corrosion foil production line that requires the use of a large amount of acid and electricity, the powder sintered foil manufacturing process has great advantages in environmental protection and energy saving.
[0003] Patent technical document CN111508712A discloses a method for manufacturing a powder sintered anode foil and an anode foil. The method for sintering the anode foil provided by the invention can ensure clean and complete degreasing, stable sintering process without overburning, and uniform pores after sintering.
[0004] However, there are still many problems in the development and manufacturing of powder sintered foil. The general process route of powder sintered foil is coating-sintering-chemical formation. During the heat treatment stage, the adhesive in the coating layer will melt and volatilize. Some adhesives will cause the tightly wound aluminum foil layers to adhere to each other, resulting in the foil roll being unable to unfold normally after sintering, causing the entire roll of product to be scrapped, resulting in a large loss.
[0005] Patent technical document CN115274304B discloses a sintered foil and a method for preparing the same. The preparation method of the invention arranges an interlayer foil at intervals in the coiled foil. The interlayer foil can effectively block the diffusion of aluminum atoms between adjacent base foils during the coiled foil sintering process, thereby alleviating the problem of adhesion between adjacent unformed foils, reducing the occurrence of edge tearing and foil breakage of the sintered foil during the coiling process, and thus improving the product quality and yield of the sintered foil.
[0006] However, this method makes the preparation process of the sintered foil more complicated and has a certain impact on the performance of the sintered foil. Summary of the invention
[0007] In view of this, the purpose of the present invention is to provide a method for preparing a powder sintered foil, so as to solve the problem that the performance of the sintered foil is affected due to adhesion of the traditional sintered foil roll.
[0008] Based on the above purpose, the present invention provides a method for preparing a powder sintered foil, comprising the following steps:
[0009] S1: Alumina powder, xylene, triethylamine and silane coupling agent are mixed, ultrasonicated for 1-2 hours, then refluxed at 110-120°C for 12-14 hours, centrifuged, washed, filtered and dried to obtain modified alumina powder, which is dispersed in an organic solvent to obtain a modified alumina suspension;
[0010] S2: mixing aluminum powder, adhesive and solvent, and homogenizing by ultrasonic treatment to obtain aluminum powder slurry;
[0011] S3: coating the slurry obtained in S2 on the surface of an aluminum foil substrate, drying to obtain a coated aluminum foil, and spraying the modified alumina suspension evenly on the coated aluminum foil, drying to obtain an aluminum foil to be sintered;
[0012] S4: sintering the aluminum foil to be sintered to obtain a sintered foil;
[0013] S5: chemically forming the sintered foil to obtain a powdered sintered anode foil;
[0014] The silane coupling agent in step S1 is hexadecyltrimethoxysilane.
[0015] Preferably, in step S1, the usage ratio of the alumina powder, xylene, triethylamine and silane coupling agent is 5-10 g: 100-200 ml: 0.6-1 g: 2-4 g.
[0016] Preferably, the mass fraction of the modified alumina suspension in step S1 is 10%-20%.
[0017] Preferably, the particle size of the aluminum oxide powder in step S1 is 1-10 μm.
[0018] Preferably, the organic solvent in step S1 is one of anhydrous ethanol, butyl acetate and N-methylpyrrolidone.
[0019] Preferably, the drying in step S1 is performed at 80-90° C. for 10-12 hours.
[0020] Preferably, the particle size of the aluminum powder in step S2 is 5-10 μm.
[0021] Preferably, the usage ratio of the aluminum powder, the adhesive and the solvent in step S2 is 100g:1-2g:150-200ml.
[0022] Preferably, the adhesive in step S2 is PVDF.
[0023] Preferably, the solvent in step S2 is one of anhydrous ethanol, butyl acetate and N-methylpyrrolidone.
[0024] Preferably, the aluminum foil substrate in step S3 is a high-purity aluminum foil with a thickness of 30 μm.
[0025] Preferably, the coating thickness of the aluminum foil coated in step S3 is 60-100 μm.
[0026] Preferably, the thickness of the modified alumina suspension sprayed in step S3 is.
[0027] Preferably, the drying in step S3 is drying at 60-70° C. for 4-6 hours.
[0028] Preferably, the specific process of sintering in step S4 is to place the aluminum foil to be sintered in a vacuum furnace and evacuate the vacuum to 10 -2 Pa, then heat from room temperature to 380-400℃ at a heating rate of 10-12℃ / min, keep warm for 3-4h, continue to heat to 580-600℃, keep warm for 2-3h.
[0029] Preferably, the specific steps of the formation in step S5 are as follows:
[0030] The sintered foil is placed in boiling water at 90-100°C for 2-10 minutes, then placed in a mixture of ammonium adipate (0.1wt%-0.3wt%) and boric acid (0.1wt%-0.15wt%) at 90-95°C for primary formation for 7-10 minutes at a formation voltage of 160-170V, washed with water, and placed in a mixture of ammonium citrate (0.01wt%-0.07wt%) and boric acid (0.1wt%-0 .3wt%) mixed solution at 85-90℃ for secondary formation for 7-10min, the formation voltage is 290-300V, after water washing, it is placed in a mixture of citric acid (0.02wt%-0.04wt%), ammonium citrate (0.03wt%-0.08wt%) and boric acid (0.4wt%-1wt%) for tertiary formation at 85-90℃ for 7-10min, the formation voltage is 450-520V, water After washing, heat treatment is performed at 300-500°C for 1-3 minutes, and then placed in a mixture of citric acid (0.02wt%-0.04wt%), ammonium citrate (0.03wt%-0.08wt%) and boric acid (0.4wt%-1wt%) at 85-90°C for post-chemical reaction for 7-10 minutes, with a chemical reaction voltage of 520V, and then placed in a 4wt% phosphoric acid solution and soaked at 60°C for 10-15 minutes. After water washing, the mixture is placed in a mixture of ammonium citrate (0.01wt%-0.07wt%) and boric acid (0.1wt%-0.3wt%) at 85-90°C for post-chemical reaction for 7-10 minutes, with a chemical reaction voltage of 520V. After water washing, the mixture is placed in a 0.5wt% diammonium phosphate solution at 70°C for 5-10 minutes. Finally, it is dried in air at 100-150°C for 5-10 minutes.
[0031] Beneficial effects of the present invention: The preparation method of the powder sintered foil of the present invention sprays a modified alumina suspension on the surface of the coated and dried aluminum foil, thereby isolating the aluminum foil that is tightly attached due to winding during the heat treatment stage, so that the foil layers do not stick together after sintering, and there will be no tearing or breaking of the foil layers during winding, and the withstand voltage, capacity and leakage current are all maintained at normal levels. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art description.
[0033] Figure 1 This is a schematic diagram of the surface microscopic morphology of the sample obtained in Example 2 of the present invention;
[0034] Figure 2 This is a schematic diagram of the surface microscopic morphology of the sample obtained in Comparative Example 2 of the present invention;
[0035] Figure 3 This is a schematic diagram of the surface microscopic morphology of the sample obtained in Comparative Example 2 of the present invention after being rolled. DETAILED DESCRIPTION
[0036] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0037] The properties of the raw materials used in the examples and comparative examples of the present invention are as follows: the particle size of the alumina powder is 5 μm; the particle size of the aluminum powder is 10 μm; the mass fraction of the modified alumina suspension is 15%; the coating thickness of the aluminum foil is 100 μm;
[0038] The specific chemical formation process of the present invention is as follows: the sintered foil is placed in boiling water at 95°C for 5 minutes, then placed in a mixture of ammonium adipate (0.2wt%) and boric acid (0.15wt%) for primary chemical formation at 93°C for 10 minutes, the chemical formation voltage is 165V, and after washing, it is placed in a mixture of ammonium citrate (0.05wt%) and boric acid (0.2wt%) for secondary chemical formation at 87°C for 7 minutes, the chemical formation voltage is 295V, and after washing, it is placed in a mixture of citric acid (0.03wt%), ammonium citrate (0.05wt%) and boric acid (0.7wt%) for tertiary chemical formation at 87°C for 8 minutes, the chemical formation voltage is 500V, and after washing, At 400°C, heat treatment was carried out for 2 minutes, and then the surface was placed in a mixture of citric acid (0.03wt%), ammonium citrate (0.05wt%) and boric acid (0.7wt%) for post-chemical reaction at 87°C for 8 minutes, with a formation voltage of 520V. Then, the surface was placed in a 4wt% phosphoric acid solution and soaked at 60°C for 13 minutes. After washing with water, the surface was placed in a mixture of ammonium citrate (0.04wt%) and boric acid (0.2wt%) for post-chemical reaction at 88°C for 8 minutes, with a formation voltage of 520V. After washing with water, the surface was immersed in a 0.5wt% diammonium dihydrogen phosphate solution at 70°C for 8 minutes. Finally, it was dried in air at 130°C for 8 minutes.
[0039] Example 1: A powder sintered foil, the specific preparation steps are as follows:
[0040] (1) 5 g of alumina powder, 100 ml of xylene, 0.6 g of triethylamine, and 2 g of hexadecyltrimethoxysilane were mixed, ultrasonicated for 1 h, and then refluxed at 110 °C for 12 h. After the reaction was completed, the mixture was allowed to stand at room temperature, centrifuged, washed, and filtered with ethanol for multiple times, and finally dried at 80 °C for 10 h to obtain modified alumina powder, which was dispersed in anhydrous ethanol to obtain a modified alumina suspension with a mass fraction of 15%;
[0041] (2) 100 g aluminum powder, 1 g PVDF and 150 ml anhydrous ethanol were mixed and homogenized by ultrasonication to obtain aluminum powder slurry;
[0042] (3) taking a high-purity aluminum foil with a thickness of 30 μm, uniformly coating the aluminum powder slurry obtained in step (2) on the surface of the aluminum foil, and then drying it at 60°C in a vacuum environment for 4-6 hours to obtain a coated aluminum foil with a coating thickness of 100 μm, and then uniformly spraying the modified alumina suspension obtained in step (1) on the surface of the coated aluminum foil (5 μm), and drying it at 65°C to obtain an aluminum foil to be sintered;
[0043] (4) The aluminum foil to be sintered is wound into a foil roll, which is then placed in a vacuum furnace and evacuated to 10 -2Pa, then the temperature was raised from room temperature to 380°C at a rate of 10°C / min, kept at that temperature for 3 h, then continued to be raised to 580°C, kept at that temperature for 2 h, and cooled to room temperature to obtain a sintered foil;
[0044] (5) The sintered foil is subjected to chemical treatment to obtain a powdered sintered anode foil.
[0045] Example 2: A powder sintered foil, the specific preparation steps are as follows:
[0046] (1) 7.5 g of alumina powder, 15 ml of xylene, 0.8 g of triethylamine, and 3 g of hexadecyltrimethoxysilane were mixed, subjected to ultrasonic treatment for 2 h, and then refluxed at 115 °C for 13 h. After the reaction was completed, the mixture was allowed to stand at room temperature, centrifuged, washed, and filtered with ethanol for multiple times, and finally dried at 85 °C for 11 h to obtain modified alumina powder, which was dispersed in anhydrous ethanol to obtain a modified alumina suspension with a mass fraction of 15%;
[0047] (2) 100 g aluminum powder, 1.5 g PVDF and 180 ml anhydrous ethanol were mixed and homogenized by ultrasonication to obtain aluminum powder slurry;
[0048] (3) taking a high-purity aluminum foil with a thickness of 30 μm, uniformly coating the aluminum powder slurry obtained in step (2) on the surface of the aluminum foil, and then drying it at 65°C in a vacuum environment for 5 h to obtain a coated aluminum foil with a coating thickness of 100 μm, and then uniformly spraying the modified alumina suspension obtained in step (1) on the surface of the coated aluminum foil (10 μm), and drying it at 65°C to obtain an aluminum foil to be sintered;
[0049] (4) The aluminum foil to be sintered is wound into a foil roll, which is then placed in a vacuum furnace and evacuated to 10 -2 Pa, then the temperature was raised from room temperature to 390°C at a rate of 11°C / min, kept at that temperature for 4 h, then the temperature was further raised to 590°C, kept at that temperature for 2 h, and cooled to room temperature to obtain a sintered foil;
[0050] (5) The sintered foil is subjected to chemical treatment to obtain a powdered sintered anode foil.
[0051] Example 3: A powder sintered foil, the specific preparation steps are as follows:
[0052] (1) 10 g of alumina powder, 200 ml of xylene, 1 g of triethylamine, and 4 g of hexadecyltrimethoxysilane were mixed, ultrasonicated for 2 h, and then refluxed at 120 °C for 14 h. After the reaction was completed, the mixture was allowed to stand at room temperature, centrifuged, washed, and filtered with ethanol for multiple times, and finally dried at 90 °C for 12 h to obtain modified alumina powder, which was dispersed in anhydrous ethanol to obtain a modified alumina suspension with a mass fraction of 15%;
[0053] (2) 100 g aluminum powder, 2 g PVDF and 200 ml anhydrous ethanol were mixed and homogenized by ultrasonication to obtain aluminum powder slurry;
[0054] (3) taking a high-purity aluminum foil with a thickness of 30 μm, uniformly coating the aluminum powder slurry obtained in step (2) on the surface of the aluminum foil, and then drying it at 70°C in a vacuum environment for 6 h to obtain a coated aluminum foil with a coating thickness of 100 μm, and then uniformly spraying the modified alumina suspension obtained in step (1) on the surface of the coated aluminum foil (8 μm), and drying it at 65°C to obtain an aluminum foil to be sintered;
[0055] (4) The aluminum foil to be sintered is wound into a foil roll, which is then placed in a vacuum furnace and evacuated to 10 -2 Pa, then the temperature was raised from room temperature to 400°C at a heating rate of 12°C / min, kept at that temperature for 4 h, then continued to be raised to 600°C, kept at that temperature for 3 h, and cooled to room temperature to obtain a sintered foil;
[0056] (5) The sintered foil is subjected to chemical treatment to obtain a powdered sintered anode foil.
[0057] Comparative Example 1: A powder sintered foil, the specific preparation steps are as follows:
[0058] (1) 7.5 g of alumina powder, 15 ml of xylene, 0.8 g of triethylamine, and 3 g of propyltrimethoxysilane were mixed, ultrasonicated for 2 h, and then refluxed at 115 °C for 13 h. After the reaction was completed, the mixture was allowed to stand at room temperature, centrifuged, washed, and filtered with ethanol for multiple times, and finally dried at 85 °C for 11 h to obtain modified alumina powder, which was dispersed in anhydrous ethanol to obtain a modified alumina suspension with a mass fraction of 15%;
[0059] (2) 100 g aluminum powder, 1.5 g PVDF and 180 ml anhydrous ethanol were mixed and homogenized by ultrasonication to obtain aluminum powder slurry;
[0060] (3) taking a high-purity aluminum foil with a thickness of 30 μm, uniformly coating the aluminum powder slurry obtained in step (2) on the surface of the aluminum foil, and then drying it at 65°C in a vacuum environment for 5 h to obtain a coated aluminum foil with a coating thickness of 100 μm, and then uniformly spraying the modified alumina suspension obtained in step (1) on the surface of the coated aluminum foil (10 μm), and drying it at 65°C to obtain an aluminum foil to be sintered;
[0061] (4) The aluminum foil to be sintered is wound into a foil roll, which is then placed in a vacuum furnace and evacuated to 10 -2 Pa, then the temperature was raised from room temperature to 390°C at a rate of 11°C / min, kept at that temperature for 4 h, then the temperature was further raised to 590°C, kept at that temperature for 2 h, and cooled to room temperature to obtain a sintered foil;
[0062] (5) The sintered foil is subjected to chemical treatment to obtain a powdered sintered anode foil.
[0063] Comparative Example 2: A powder sintered foil, the specific preparation steps are as follows:
[0064] (1) dispersing alumina powder in anhydrous ethanol to obtain an alumina suspension with a mass fraction of 15%;
[0065] (2) 100 g aluminum powder, 1.5 g PVDF and 180 ml anhydrous ethanol were mixed and homogenized by ultrasonication to obtain aluminum powder slurry;
[0066] (3) taking a high-purity aluminum foil with a thickness of 30 μm, uniformly coating the aluminum powder slurry obtained in step (2) on the surface of the aluminum foil, and then drying it at 65°C in a vacuum environment for 5 h to obtain a coated aluminum foil with a coating thickness of 100 μm, and then uniformly spraying the alumina suspension obtained in step (1) on the surface of the coated aluminum foil (10 μm), and drying it at 65°C to obtain an aluminum foil to be sintered;
[0067] (4) The aluminum foil to be sintered is wound into a foil roll, which is then placed in a vacuum furnace and evacuated to 10 -2 Pa, then the temperature was raised from room temperature to 390°C at a rate of 11°C / min, kept at that temperature for 4 h, then the temperature was further raised to 590°C, kept at that temperature for 2 h, and cooled to room temperature to obtain a sintered foil;
[0068] (5) The sintered foil is subjected to chemical treatment to obtain a powdered sintered anode foil.
[0069] Comparative Example 3: A powder sintered foil, the specific preparation steps are as follows:
[0070] (1) 100 g aluminum powder, 1.5 g PVDF and 180 ml anhydrous ethanol were mixed and homogenized by ultrasonication to obtain aluminum powder slurry;
[0071] (2) taking a high-purity aluminum foil with a thickness of 30 μm, uniformly coating the aluminum powder slurry obtained in step (1) on the surface of the aluminum foil, and then drying it in a vacuum environment at 65°C for 5 h to obtain a coated aluminum foil with a coating thickness of 100 μm, and intermittently winding the coated aluminum foil with an aluminum alloy foil with a thickness of 10 μm to form a foil roll;
[0072] (3) Place the foil roll in a vacuum furnace and evacuate to 10 -2 Pa, then the temperature was raised from room temperature to 390°C at a rate of 11°C / min, kept at that temperature for 4 h, then the temperature was further raised to 590°C, kept at that temperature for 2 h, and cooled to room temperature to obtain a sintered foil;
[0073] (4) The sintered foil is subjected to chemical treatment to obtain a powdered sintered anode foil.
[0074] Performance Testing
[0075] The sintered foils obtained in the embodiment and the comparative example were rolled up and their adhesion was observed. The test results are shown in Table 1.
[0076] Table 1 Performance test results
[0077]
[0078] The performance of the sintered powder anode foil obtained in the embodiment and the comparative example was tested, and the test results are shown in Table 2;
[0079] Table 2 Performance test results
[0080]
[0081] Data Analysis:
[0082] It can be seen from the data in Table 1 that the present invention sprays a modified alumina suspension on the surface of the coated and dried aluminum foil, thereby isolating the aluminum foil that is tightly attached due to winding during the heat treatment stage, so that the foil layers do not stick together after sintering and rolling, and there will be no tearing or breaking of the foil layers. The surface of the thin layer is very uniform without any wrinkles.
[0083] It can be seen from Example 2 and Comparative Examples 1 and 2 in Table 1 that the present invention modifies the alumina powder so that the particle distribution in the modified alumina suspension is more uniform, and a more uniform isolation layer can be formed in the subsequent spraying and sintering processes, thereby ensuring that the foil edge tearing and foil breaking caused by adhesion will not occur after the sintered foil is rolled. In addition, when the alumina powder is modified with a long-chain silane coupling agent and then dispersed in a solvent, the long chains are entangled with each other to form a physical interlocking structure. In the subsequent spraying and sintering processes, a more uniform, dense and structurally stable isolation layer can be formed, further ensuring that the sintered foil will not stick after the foil is rolled.
[0084] It can be seen from Table 2 that the withstand voltage, capacity and leakage current of the powder sintered foil of the present invention are all maintained at normal levels.
[0085] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A method for preparing a powder sintered foil, characterized in that: The following steps are involved: S1: Alumina powder, xylene, triethylamine and silane coupling agent are mixed, ultrasonicated for 1-2 hours, then refluxed at 110-120°C for 12-14 hours, centrifuged, washed, filtered and dried to obtain modified alumina powder, which is dispersed in an organic solvent to obtain a modified alumina suspension; S2: mixing aluminum powder, adhesive and solvent, and homogenizing by ultrasonic treatment to obtain aluminum powder slurry; S3: coating the slurry obtained in S2 on the surface of an aluminum foil substrate, drying to obtain a coated aluminum foil, and spraying the modified alumina suspension evenly on the coated aluminum foil, drying to obtain an aluminum foil to be sintered; S4: sintering the aluminum foil to be sintered to obtain a sintered foil; S5: chemically forming the sintered foil to obtain a powdered sintered anode foil; The silane coupling agent in step S1 is hexadecyltrimethoxysilane.
2. The method for preparing a powder sintered foil according to claim 1, characterized in that: The usage ratio of the alumina powder, xylene, triethylamine and silane coupling agent in step S1 is 5-10g:100-200ml:0.6-1g:2-4g.
3. The method for preparing a powder sintered foil according to claim 1, characterized in that: The mass fraction of the modified alumina suspension in step S1 is 10%-20%.
4. The method for preparing a powder sintered foil according to claim 1, characterized in that: The usage ratio of the aluminum powder, the adhesive and the solvent in step S2 is 100g:1-2g:150-200ml.
5. The method for preparing a powder sintered foil according to claim 1, characterized in that: In step S2, the adhesive is PVDF, and the solvent is one of anhydrous ethanol, butyl acetate, and N-methylpyrrolidone.
6. The method for preparing a powder sintered foil according to claim 1, characterized in that: The aluminum foil substrate in step S3 is a high-purity aluminum foil with a thickness of 30 μm.
7. The method for preparing a powder sintered foil according to claim 1, characterized in that: The coating thickness of the aluminum foil in step S3 is 60-100 μm, and the thickness of the modified aluminum oxide suspension sprayed in step S3 is 5-10 μm.
8. The method for preparing a powder sintered foil according to claim 1, characterized in that: The specific process of sintering in step S4 is to place the aluminum foil to be sintered in a vacuum furnace and evacuate the vacuum to 10 -2 Pa, then heat from room temperature to 380-400℃ at a heating rate of 10-12℃ / min, keep warm for 3-4h, continue to heat to 580-600℃, keep warm for 2-3h.
9. The method for preparing a powder sintered foil according to claim 1, characterized in that: The formation described in step S5 comprises the following steps: The sintered foil is placed in boiling water at 90-100°C for 2-10 minutes, then placed in a mixture of ammonium adipate (0.1wt%-0.3wt%) and boric acid (0.1wt%-0.15wt%) at 90-95°C for primary formation for 7-10 minutes at a formation voltage of 160-170V, washed with water and placed in a mixture of ammonium citrate (0.01wt%-0.07wt%) and boric acid (0.1wt%-0. 3wt%) mixed solution at 85-90℃ for secondary formation for 7-10min, the formation voltage is 290-300V, after washing with water, placed in a mixture of citric acid (0.02wt%-0.04wt%), ammonium citrate (0.03wt%-0.08wt%) and boric acid (0.4wt%-1wt%) at 85-90℃ for tertiary formation for 7-10min, the formation voltage is 450-520V, water After washing, heat treatment is performed at 300-500°C for 1-3 minutes, and then placed in a mixture of citric acid (0.02wt%-0.04wt%), ammonium citrate (0.03wt%-0.08wt%) and boric acid (0.4wt%-1wt%) for post-chemical reaction at 85-90°C for 7-10 minutes, with a formation voltage of 520V, and then placed in a 4wt% phosphoric acid solution and soaked at 60°C for 10-15 minutes. After water washing, the mixture is placed in a mixture of ammonium citrate (0.01wt%-0.07wt%) and boric acid (0.1wt%-0.3wt%) for post-chemical reaction at 85-90°C for 7-10 minutes, with a formation voltage of 520V. After water washing, the mixture is immersed in a 0.5wt% diammonium phosphate solution at 70°C for 5-10 minutes. Finally, it is dried in air at 100-150°C for 5-10 minutes.
Citation Information
Patent Citations
Manufacturing method of powder sintered anode foil and anode foil
CN111508712A
Sintered foil and method for preparing the same
CN115274304B
Bearing improvement process for reducing vibration intensity of chemical pump
CN112064019A
Laser scanning auxiliary laminated foil preparation method
CN116100027A
Preparation method of high-hardness high-temperature steam oxidation resistant composite structure coating
CN116837315A